2023
DOI: 10.1021/acs.jpcc.2c08630
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-Sensitive Photodetection of Anisotropic 2D Black Arsenic

Abstract: A lateral phototransistor structure based on mechanically exfoliated multilayer black arsenic (b-As) is produced to test its in-plane anisotropy of photoelectrical properties. First, the morphology and structure of the b-As flake are investigated with respect to light polarization and crystal structure orientation. Then, the Raman modes, demonstrating a strong anisotropic nature of twofold symmetry for in-plane vibrations and fourfold symmetry for out-of-plane vibrations, allow us to define the armchair and zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Furthermore, the linear DR can be tuned by flexibly adjusting the extrinsic strain. Specifically, under 4.5% tensile strain, the linear DR can reach up to ≈2, which is comparable to those of low-dimensional vdWMs with intrinsic anisotropy arising from the low-symmetry crystal structures [121,126,238].…”
Section: Strain Engineeringmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, the linear DR can be tuned by flexibly adjusting the extrinsic strain. Specifically, under 4.5% tensile strain, the linear DR can reach up to ≈2, which is comparable to those of low-dimensional vdWMs with intrinsic anisotropy arising from the low-symmetry crystal structures [121,126,238].…”
Section: Strain Engineeringmentioning
confidence: 81%
“…Thus far, researchers have prepared numerous polarized photodetectors based on a variety of anisotropic 2D vdWMs, including group VA semiconductors [71, [125][126][127][128][129], nonprecious transition metal chalcogenides (MX 2 [130][131][132][133][134], MX 3 [135][136][137][138][139][140][141], MX 5 [142]), IIIA-VIA compounds [123,143,144], IVA-VA compounds [123,[145][146][147][148][149][150][151], IVA-VIA compounds [120,121,[152][153][154][155][156], precious transition metal chalcogenides [157][158][159][160][161][162][163][164], multielemental vdWMs [72, 73, 165-173], etc. For clarity, table 2 has summarized the key performance metrics of various 2D vdWM polarizationsensitive optoelectronic devices.…”
Section: D Vdwm Polarized Photodetectorsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Traditional photodetectors that convert optical signals to electrical signals are primarily based on InGaAs, GaN, and Si that require elaborate lm growth techniques. [12][13][14][15][16][17][18][19][20][21] More recently solution processible semiconductor-based hybrid perovskites and organic polymers have shown promise in applications like optical communications, imaging, chemical and biological sensing. However, direct gap solution processible semiconductors with reduced complexity in manufacturing, exible form factors accompanied by high absorption and carrier lifetime are always desirable over disordered materials in these applications.…”
Section: Introductionmentioning
confidence: 99%
“…Black phosphorus (bP), with a bulk direct energy band gap of 0.33 eV (3.7 μm), has shown great promise for high-performance mid-IR photodetectors and emitters . Notably, as compared to conventional III–V and II–VI semiconductors with similar band gaps, bP exhibits a lower Auger recombination rate due to its more symmetric electron/hole effective mass. ,, To further the applications of black phosphorus toward longer wavelengths, various techniques have been demonstrated, including applying compressive strain, , tuning the electric field, applying pressure, and alloying with other group V elements such as arsenic. Alloying is promising, as it can be directly incorporated into existing device designs.…”
mentioning
confidence: 99%
“…In the past few years, various studies have demonstrated mid-IR photodetectors (phototransistor and photodiode, with high responsivity) with black phosphorus arsenic (bPAs) alloys, while electroluminescence of a bPAs heterostructure and simulated emission of bPAs in a cavity at 3.4–4.7 μm have been reported recently. Despite considerable research highlighting bPAs mid-IR optoelectronic device potential, ,,, detailed quantitative optical characterization as a function of As concentration is still lacking. Such data are needed for optimal design of bPAs optoelectronic devices while projecting their performance limits.…”
mentioning
confidence: 99%